The People's Voice is Manipulated through Election Vote Counting: Indications of Structured Fraud and Its Impact on Democratic Integrity - Astrid Ramadhany; Muhammad Arsy; Imran Eka Saputra (Faculty of Law, Universitas Muslim Indonesia, 2025)
Vote-count manipulation is an electoral crime that can undermine the legitimacy of election results and reduce public trust in democratic processes. This study aimed to analyze the legal framework governing the criminal offense of vote-count fraud in general elections in Indonesia, to examine the mechanisms for handling and enforcing the law against such violations, and to assess the application of criminal sanctions under the applicable laws and regulations. This research used a normative legal method with a statutory approach and examined relevant legislation, legal principles. The study found that manipulation of vote-count results was explicitly prohibited and subject to criminal sanctions under Indonesian electoral laws. The enforcement mechanism for electoral crimes was carried out through the Integrated Law Enforcement Center (Sentra Gakkumdu), which integrated the roles of the Election Supervisory Body (Bawaslu), the Police, and the Prosecutor’s Office to ensure effective enforcement and legal certainty in handling electoral criminal cases. This study concludes that strengthening the professionalism and integrity of law enforcement officials is essential to prevent and effectively address vote-count fraud in elections, thereby safeguarding democratic legitimacy and public trust in the electoral system.